Inside/Outside : A Physician's Journey with Breast Cancer - Gilsdorf, Janet R. (Book collections on Project MUSE., 2006)
To doctors, cancer means cells growing out of control; to patients, cancer means a life spinning out of control. Janet R. Gilsdorf, who writes with quiet but devastating honesty about her experience with breast cancer, offers an eye-opening glimpse, through her unique dual perspective as physician and patient, of both sides of the medical divide. The medical system delivers cures, answers, and relief from pain to those who seek its help, but it can also offer misinformation, shattered expectations, horrible options, and inhumane consideration of the people it is supposed to serve. As Gils.